2019
DOI: 10.1111/ncn3.12267
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of patients with myasthenia gravis accompanied by psychiatric disorders

Abstract: Background Patients with myasthenia gravis (MG) often suffer from psychiatric disorders, such as anxiety disorder and depression. These psychiatric disorders may affect the treatment of MG. Aim This study aimed to closely examine psychiatric disorders in MG patients and identify influential factors. Methods We retrospectively surveyed 103 MG patients regarding clinical characteristics, and development and exacerbation of psychiatric disorders. In addition, we compared comorbid psychiatric disorders in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“…Furthermore, they have found that psychiatric disorders were less frequent in patients with concurrent myositis who were treated with chronic oral steroids. (31) Our study, likewise failed to demonstrate this association. Thymectomy, on the other hand, has been regarded as one of the standards of treatment in thymomatous and nonthymomatous anti-AChR positive MG, to reduce medication requirement and disease severity overtime.…”
Section: Discussioncontrasting
confidence: 68%
“…Furthermore, they have found that psychiatric disorders were less frequent in patients with concurrent myositis who were treated with chronic oral steroids. (31) Our study, likewise failed to demonstrate this association. Thymectomy, on the other hand, has been regarded as one of the standards of treatment in thymomatous and nonthymomatous anti-AChR positive MG, to reduce medication requirement and disease severity overtime.…”
Section: Discussioncontrasting
confidence: 68%
“…Disabilities resulting from MG often affect patients’ quality of life and interfere with their daily routine and activity (Vitturi et al., 2021 ). Additionally, Instability of MG symptoms, prolonged illness, and treatment with steroids can cause psychiatric symptoms in MG patients (Yamamoto et al., 2019 ). Mood disorders are very common among patients with neurological conditions and MG patients are no exception.…”
Section: Discussionmentioning
confidence: 99%
“…It is predicted that MG affects 36,000 to 60,000 patients in the United States and more than 700,000 people worldwide annually. Age and sex are important factors in the incidence and prevalence of MG (Yamamoto et al., 2019 ). In MG, the transmission of nerve impulses to the muscles is disrupted.…”
Section: Introductionmentioning
confidence: 99%